Does Paternity Leave Matter for Female Employment in Developing Economies? : Evidence from Firm Data - Amin, Mohammad; Islam, Asif; Sakhonchik, Alena (World Bank, Washington, DC, 2016)
For a sample of 53 developing countries, the results show that women's employment among private firms is significantly higher in countries that mandate paternity leave versus those that do not. A conservative estimate suggests an increase of 6.8 percentage points in the proportion of women workers associated with the mandating of paternity leave.